Implementasi Theory of Constraints untuk Penurunan Waktu Tunggu Pelayanan Resep Obat - Nurtania, Rhesta; Tazkiyah, Sururut; Rochmah, Thinni Nurul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to increase the efficiency of prescription service time at the Outpatient Pharmacy Installation (IFRJ) of Semen Gresik Hospital through the implementation of ToC by providing recommendations for improvement. The method used is observational with a cross-sectional design, and the Theory of Constraints (TOC) is applied to identify and overcome the main obstacles in the service process prescription, as well as develop performance improvement solutions. The research participants consisted of pharmaceutical personnel who had worked for more than one year, including 1 Head of Pharmacy Installation, 1 Head of the Outpatient Pharmacy Service Team, and 1 Pharmaceutical Technical Personnel. Observations were made based on recipes served for two weeks. The research population was 14,226 prescriptions for one month, with the sample consisting of 193 finished medicine prescriptions and 180 concocted prescriptions taken by simple random sampling. The research results show that the main obstacles lie in the process of prescription entry and drug delivery as well as KIE (Communication, Information and Education). The prescription process uses a single line queuing system through seven main stages, with an overall average waiting time of 32.82 minutes. The longest process was preparing medicine with an average time of 12.22 minutes, and finished medicine prescriptions had a waiting time that did not meet the highest standards (26.1%) with an average waiting time of 24.18 minutes. Recommendations for improvement include optimizing work flow with information technology, increasing coordination between units, and increasing the number of pharmacists. Simultaneously, the implementation of ToC through recommendations for improvements is expected to increase service efficiency and patient satisfaction at IFRJ Semen Gresik Hospital. Keywords: Communication, Information, and Education, Efficiency of Service, Patient Satisfaction, Prescription Service, Theory of Constraints, Wait Time